Predicting the future of human-coyote interactions in Edmonton using differential equations - Marklund, Sarah (My University, 2024)
In this paper, a system of differential equations is formulated to study the issue of human-coyote interactions in Edmonton. The system’s asymptotic behaviour is examined to predict the size of the coyote population in the future, as well as the number of bold coyotes and individuals concerned about coyotes. These values are shown to stabilize, indicating a need for better management to fully eliminate bold coyote behaviour.
Keywords: human-animal interactions; coyote behaviour; urban coyote populations; mathematical models